The Concept of Being in Traditional African Communalism and Its Implications in the Life of an African Man - Uzondu, Ignatius (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2025)
The inquiry into the nature and attributes of Being has been a foremost task of philosophy, beginning from ancient times and down to this era. But then just as there are the various conceptualizations of “Being” from various schools of thought and from unique continental philosophical traditions, so also, there is the unique understanding of “Being” from the point of view of African communalism. It is therefore our task in this paper to articulate the contextual understanding of Being in the theory and practice of African Communalism, not just as an intellectual exercise, but also as an ideological base for some African belief systems and as guide to actual lived experience of Africans to this day. Using the methods of hermeneutics and critical phenomenology, this paper strategically digs into a typical “metaphysical” attribute of African understanding of man, not just as “individual” but also as that “individual whose life and purpose can only attain meaning and fulfillment as an intrinsic member of the Group whose collective decisions and actions contribute to defining one’s existence (the individual) here on earth, and in the after-life. The main purpose for this inquiry is to underscore the reasons behind the perceived African mindset and attitude to life, and what other implications the concept of “Being” from the theoretical formulations of African Communalism has for continued appreciation of life for Africans.